A lean neck mass clinic model: Adding value to care. (8th August 2015) - Tillman, Brittny N.; Glazer, Tiffany A.; Ray, Amrita; Brenner, J. Chad; Spector, Matthew E.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To demonstrate that ultrasound‐guided fine needle aspiration (USFNA) with on‐site cytopathologic analysis eliminates unnecessary diagnostic testing, return visits, and repeat procedures and optimizes quality of care. Study Design Retrospective cohort. Methods Sixty‐one new patients (28 female; 33 male; age range = 19–85 years) were seen in our dedicated neck mass clinic over a 1‐year period. All patients underwent USFNA of masses located in neck levels I–VI (n = 40), parotid gland (n = 20), or parapharyngeal space (n = 1). Each patient underwent two USFNA passes followed by on‐site cytopathologic analysis with additional passes if required for diagnosis. Results Diagnosis was made in 93.4% (n = 57) of patients, allowing for counseling and treatment planning at the first visit. To obtain a diagnosis, more than half (57.4%, n = 35) of our patients required additional passes, which implies that they would have required an additional visit without on‐site cytopathologic analysis. Treatment included observation in 42.6% (n = 26) of patients, surgery in 32.8 % (n = 20) of patients, and nonsurgical treatment (chemotherapy, radiation, other) in 24.6% (n = 15) of patients. The average time from check‐in to checkout including the clinic visit, biopsy, and treatment counseling was 103 minutes, and the average round trip mileage traveled per patient was 127.6 miles. Conclusions The adult neck mass is a commonly encountered scenario in otolaryngology. For the patient, this can be a stressful situation in which timely and accurate diagnosis is critical. A dedicated lean neck mass clinic model with USFNA and on‐site cytopathologic analysis can be both an efficient part of one's practice and a valuable addition to patient care. Level of Evidence 4 Laryngoscope, 125:2509–2513, 2015